Proses Jual Beli Hak atas Tanah dengan Pembiayaan Kredit dari Bank - I Kadek Surya Wirawan; I Nyoman Putu Budiartha; Luh Putu Suryani (Warmadewa Press, 2022)
In this truly globalized world, living things become social beings who interact with each other. One of the conversations people have in civil dialogue is to agree on something. One of them is the sale and purchase of land rights with credit financing from banks. People often do not understand the legality of land credited through banks, so from this problem the purposes of this study are to find out the legality of the process of buying and selling land rights with credit financing from banks and procedures for buying and selling land rights with credit financing from banks. This study uses a normative research type with a case approach. Sources of data used in the form of primary and secondary legal sources. The technique of collecting legal materials that the author uses in this research is a literature study. The legal material analysis technique used is descriptive technique. The findings reveal that the principle of contractual independence as regulated in BGB 1338, and every contract made will apply to the parties to the contract and function as a supplier's rights. So that the debtor can determine the reason for receiving deposits or guarantees, bank guarantees, or PPJB status guarantees.